Rosuvastatin inhibit the cell proliferation and the expression of angiogenic factors Vascular Endothelial Growth Factor and Matrix-Metalloproteinase-9 in DU-145 human prostate cancer cells - Abdolkhaleg Deezagi; Armaghan Jamalnia; Hanieh Jaefary (International Journal of Immunotherapy and Cancer Research - Peertechz Publications, 2021)
Abstract Background: Pathophysiology angiogenesis refers to uncontrollable endothelium capillary proliferation, it can be seen in diseases such as growth and metastasis of tumors. The aim of this was to study the effects of Rosuvastatin on the cell growth and expression of the Vascular Endothelial Growth Factor (VEGF) and matrix metal proteases (MMP-9) genes in human prostate cancer DU-145 cells. Methods: DU145 cells were cultured in RPMI medium containing 10% FBS, then treated with Rosuvastatin (5-100μM) for 96 hr. The cell proliferation was analyzed by cell counting, MTT and trypan blue tests. Nitric oxide production was assayed by Greis test. The wound healing scratching test was employed to analyze the cell migration. The VEGF and MMP-9 gene expression was analyzed by RT-PCR.  Results and conclusion: The Rosuvastatin can cause a higher rate of inhibition in cell proliferation and growth which accomponish by inhibition of cell migration in scratching assay. Considerably, decrease in cell growth and migration was observed in half of the DU145 cells, treated by 25 µM rosuvastatin. NO assay showed that high concentrations of the medication are able to reduce NO production and release. Moreover, VEGF-A and MMP-9 genes expression could be inhibited by 50 µM of Rosuvastatin.